2018
DOI: 10.3727/096504018x15188340975709
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA CCAL Promotes Papillary Thyroid Cancer Progression by Activation of NOTCH1 Pathway

Abstract: Long non-coding RNA CCAL has been reported to promote tumor progression in various human cancers, including hepatocellular carcinoma, osteosarcoma, and colorectal cancer. However, the role of CCAL in papillary thyroid cancer remains largely unknown. In the present study, we found that the expression of CCAL was upregulated in papillary thyroid tumor tissues compared to adjacent normal tissues. Moreover, the expression of CCAL was positively related with papillary thyroid cancer severity and TNM stage, and pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Finally, our experimental findings also showed that LINC00284 activated the Notch signaling pathway by increasing ADAM12 expression. The aforementioned activation of the Notch signaling pathway has also been previously implicated in the progression of PTC ( 36 ). The Notch pathway directly combines events at the cell membrane with transcriptional regulation.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, our experimental findings also showed that LINC00284 activated the Notch signaling pathway by increasing ADAM12 expression. The aforementioned activation of the Notch signaling pathway has also been previously implicated in the progression of PTC ( 36 ). The Notch pathway directly combines events at the cell membrane with transcriptional regulation.…”
Section: Discussionmentioning
confidence: 96%
“…It is of interest that several of the molecular processes known to be involved in glioblastoma pathogenesis are either confirmed or identified as epigenetically regulated in this study. NOTCH 1 signalling has been previously described as activated in glioblastoma, including via epigenetic regulation mediated through H3K4me3 58 , and our data confirm this regulation hence also lending support to our experimental approach. We show loss of H3K36me3 and concomitant repression of the beta-catenin degradation pathway via Axin in keeping with existing knowledge of over activation of WNT pathway in glioblastoma 29 .…”
Section: Discussionsupporting
confidence: 88%
“…The G allele of rs619586 could remarkably reduce MALAT1 expression to promote PTC apoptosis, which was recognized a protective factor of PTC susceptibility [23]. Other reports also illuminated high expression of ABHD11-AS1, FOXD2-AS1, and CCAL portended poor clinical outcome of PTC sufferers [24][25][26]. Till now, the roles of LINC00284 in breast cancer [16], ovarian cancer [17], gastric cancer [27], and hepatocellular carcinoma [18] have been preliminarily investigated, while its biological effects in PTC weren't illustrated.…”
Section: Discussionmentioning
confidence: 98%